Implementasi Pengelolaan dan Administrasi Kesiswaan di SMP Negeri 2 Kepung Tahun Ajaran 2020/2021 - Lailatul Munawaroh; Khoirotul Izzah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
This research discusses the management and administration of students in SMP Negeri 2 Kepung in the 2020/2021 school year which aims to find out how to implement student management and administration in SMP Negeri 2 Kepung. Data collection techniques used are observation, interviews and documentation. The results showed that the implementation of student administration management in SMP Negeri 2 Kepung has been running in accordance with the purpose of education, namely regulating the activities of learners so that these activities are in the process of teaching and learning in schools, the teaching and learning process can run smoothly, orderly, regularly so as to provide contributions to the achievement of learning goals in school. Thus the school student administration is structured to provide guidance for the organizers and managers of student administration can be orderly and organized so as to achieve school goals and channel and develop the ability of intelligence, talent of learners. For this reason, student administration is very necessary because it holds a hand and has a very important role in developing the ability and potential of qualified learners in accordance with educational goals.